Functional donor-site morbidity after soleus muscle-flap procedure in the treatment of lower limb severe injuries - Riccio, Michele; Zingaretti, Nicola; Verdini, Federica; Marchesini, Andrea; De Francesco, Francesco; Parodi, Pier Camillo (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2019)
Background The gastrocnemius and soleus muscle flaps are the most commonly used transfer flaps to treat lower limb severe lesions. The use of the muscle as coverage tissuemay incur in functionality loss and motor control deficits. The aim of this study is to assess whether functional deficits are present during gait, posture and heel rise test (HRT).Method From 2008–2013 we treated 9 patients suffering from complex injury of the lower third of the leg (Gustilo III B). A population of 9 patients (group A) was examined after reconstruction with a soleus muscle flap. The results were compared with a control population (group B: 9 patients). Each patient performed at least 3 gait tests at a fast pace, 2 posture tests and 2 HRT on an inclined plane.Results Gait parameters for group A: Spatio-temporal parameters such as step length, cadence were reduced compared to the homolateral leg (p < 0.05). The initial double support phase was shorter in relation to the final phase and the first peak in the vertical ground reaction component was reduced compared to the contralateral leg.Posture for the group A: the mediolateral excursion (during open- and closed-eyes test) and the related mean velocity (in the open-eyes test) were significantly lower compared to the control group (p < 0.05).HRT for group A: the number of rises and relative height and angular excursion were reduced in the operated leg in relation to the control group (p < 0.05) and to the contralateral leg.Conclusion The patients treated with the soleus muscle used as tissue defect coverage completely recovered the ability to walk but showed some deficits in kinetic parameters during the body weight-loading phase. During gait prolonged muscle activity compared to controls was observed. The absence of soleus (group A) revealed no significant alterations in postural control. However, the HRT remained the most relevant test to measure patients’ performance when treated with soleus flap in relation to the control group.
Keywords: EMG; gait; walking speed; soleus flap; heel rise; limb saving surgery